Promoting Cooperation between Educational Institutions and Workplaces : Models of Integrative Pedagogy and Connectivity Revisited - Tynjälä, Päivi [Verfasser]; Virolainen, Maarit [Verfasser]; Heikkinen, Hannu L.T. [Verfasser]; Virtanen, Anne [Verfasser] (My University, 2020)
"This theoretical review reflects on the development and application of the Integrative Pedagogical model as well as the Connective model investigating the organisation of learning in the interface between educational institutions and workplaces. The article explores the aspects that these two models emphasise, and identifies similarities and differences between them. Key studies on these approaches were reviewed to accomplish the task. The review shows how integrative pedagogy takes the individual's learning as its starting point and how educators can support students by encouraging them to combine theoretical knowledge, experience and self-regulation in learning. While this model is pedagogical, the connectivity approach is more sociological in nature and highlights interpretative change concerning knowledge in the process of recontextualisation. Both approaches emphasise the role of communities of practice in building the zone of proximal development, and have been applied to conceptualise collaborative arrangements between educational institutions and work organisations." (authors' abstract; BIBB-Doku)

Dieser theoretische Überblick befasst sich mit der Entwicklung und Anwendung des Integrativen Pädagogischen Modells sowie des Konnektivitätsmodells zur Untersuchung der Organisation des Lernens an der Schnittstelle zwischen Bildungseinrichtungen und Arbeitswelt. Der Beitrag untersucht Aspekte, die beide Modelle hervorheben, und identifiziert Gemeinsamkeiten und Unterschiede zwischen ihnen. Einschlägige Studien zu diesen Ansätzen wurden zur diesem Zweck gesichtet und ausgewertet. Der Überblick zeigt, wie die integrative Pädagogik das Lernen des Einzelnen als Ausgangspunkt nimmt und wie Lehrpersonen die Lernenden unterstützen können, indem sie diese ermutigen, theoretisches Wissen, Erfahrung und Selbstregulierung beim Lernen zu kombinieren. Während dieses Modell der Pädagogik entstammt, hat der Connectivity-Ansatz seinen Ursprung eher in der Soziologie und zeigt interpretative Veränderungen des Wissens im Prozess der Rekontextualisierung auf. Beide Ansätze betonen die Rolle der Praxisgemeinschaften beim Aufbau einer "Zone der proximalen Entwicklung" und wurden zur Konzeptualisierung des Zusammenwirkens zwischen Bildungseinrichtungen und Arbeitsorganisationen angewandt. (Autorenreferat; BIBB-Doku)
Keywords: L 2.1 Lernformen; Lernen und Arbeiten; Lernen am Arbeitsplatz; Modell